Blastocystis ST-1 is associated with Irritable Bowel Syndrome-diarrhoea (IBS-D) in Indonesian adolescences() - Kesuma, Yudianita (Parasite Epidemiol Control, 2019)
OBJECTIVE: IBS is a functional gastrointestinal disorder and commonly presents in children and adolescences, presented as diarrhoea, constipation or mixed type. Blastocystis is a common intestinal protozoa found worldwide, which pathogenicity is still controversial. This study aimed to identify the risk factors of IBS, the association between IBS types with Blastocystis subtypes and analyse Blastocystis pathogenicity. DESIGN: A comparative cross-sectional study was conducted among senior high school students. Rome III Criteria for IBS diagnosis, questionnaires on the risk factors of IBS and types of IBS were recorded. Students were further selected and classified into IBS and non-IBS groups to analyse the association between IBS, IBS types with Blastocystis infection and its subtypes. Direct microscopic stool examination to identify single Blastocystis infection was performed, followed by culture in Jones' medium, PCR, sequencing of 18S rRNA and phylogenetic analysis to determine Blastocystis subtype. Data was analysed using SPSS v22.0 and P value <0.05 was considered statistically significant (95% confidence intervals). RESULTS: IBS was found in 30.2% of 454 students, consisted of 33.3% IBS Diarrhoea, 27.7% IBS Mixed, 27.7% IBS Unclassified and 11.1% IBS Constipation. Major risk factors to IBS consisted of family history of recurrent abdominal pain, abuse, bullying and female gender in respective order (OR 3.6–2.1). Blastocystis ST-1 was significantly associated to IBS-D with 2.9 times risk factor. CONCLUSIONS: Blastocystis infection is a risk factor to develop IBS-D type in adolescence; Blastocystis ST-1 can be regarded as a pathogenic subtype.